Learner-generated content and engagement in second language task performance - Lambert, Craig; Philp, J.; Nakamura, S. (Arnold, 2016)
This study investigates the benefits of designing second language (L2) learning tasks to operate on learner-generated content (related to actual content in their lives and experiences) as opposed to teacher-generated content typical of current approaches to L2 task design (fictitious ideas and events created to provide an opportunity for meaningful language use). Thirty-two Japanese learners completed parallel versions of narrative tasks, which operated on learner-generated content and teacher-generated content respectively. Learner engagement in L2 use was measured in terms of behavioral, cognitive, and social components: behavioral engagement was measured in terms of effort and persistence in task completion; cognitive engagement in terms of attention to elaborating and clarifying content; and social engagement in terms of participants’ affiliation in the discourse. Results indicate that tasks operating on learner-generated as opposed to teacher-generated content had positive effects on all aspects of engagement in L2 use during task performance. Furthermore, participants’ affective responses to the respective conditions as reflected in a post-performance questionnaire corroborated the results for performance. This indicates that learners were also more affectively engaged in the performance of the tasks in the learner-generated content condition than they were in those in the teacher-generated content condition.